The effect of material strength on the behaviour of concrete‐filled steel elements - Brauns, Janis; Rocens, Karlis (Journal of Civil Engineering and Management, 2004)
Composite columns and beams are a combination of concrete and steel elements realising the advantages of both types of materials. According to codes for concrete‐filled column, the plastic resistance of the cross‐section is given as a sum of the components and taking into account the effect of confinement in case of circular sections. In this study the stress state in composite column is determined taking into account non‐linear relationship of the modulus of elasticity and Poisson’s ratio on the stress level in the concrete core. It has been determined that the effect of confinement occurs at a high stress level when structural steel acts in tension and concrete works in lateral compression. The stress state and load bearing capacity of section in bending is determined taking into account non‐linear dependence on position of neutral axis. Because the ultimate limit state of material is not attained for all the parts simultaneously, to improve the stress state of a composite element and to prevent the possibility of a failure the appropriate strength of concrete and steel should be used. The safety of high‐stressed composite structures can be achieved by using ultra‐high‐performance concrete (UHPC). First Published Online: 14 Oct 2010